Titanium stable isotopic variations in chondrites, achondrites and lunar rocks. (15th September 2017) - Greber, Nicolas D.; Dauphas, Nicolas; Puchtel, Igor S.; Hofmann, Beda A.; Arndt, Nicholas T.
Abstract: Titanium isotopes are potential tracers of processes of evaporation/condensation in the solar nebula and magmatic differentiation in planetary bodies. To gain new insights into the processes that control Ti isotopic variations in planetary materials, 25 komatiites, 15 chondrites, 11 HED-clan meteorites, 5 angrites, 6 aubrites, a martian shergottite, and a KREEP-rich impact melt breccia have been analyzed for their mass-dependent Ti isotopic compositions, presented using the δ 49 Ti notation (deviation in permil of the 49 Ti/ 47 Ti ratio relative to the OL-Ti standard). No significant variation in δ 49 Ti is found among ordinary, enstatite, and carbonaceous chondrites, and the average chondritic δ 49 Ti value of +0.004 ± 0.010‰ is in excellent agreement with the published estimate for the bulk silicate Earth, the Moon, Mars, and the HED and angrite parent-bodies. The average δ 49 Ti value of komatiites of −0.001 ± 0.019‰ is also identical to that of the bulk silicate Earth and chondrites. OL-Ti has a Ti isotopic composition that is indistinguishable from chondrites and is therefore a suitable material for reporting δ 49 Ti values. Previously published isotope data on another highly refractory element, Ca, show measurable variations among chondrites. The decoupling between Ca and Ti isotope systematics most likely occurred during condensation in the solar nebula. Aubrites exhibit significant variations in δ 49 Ti, from −0.07 to +0.24‰. This is likely due to the uniquely reducing conditions under which the aubrite parent-body differentiated, allowing chalcophile Ti 3+ and lithophile Ti 4+ to co-exist. Consequently, the observed negative correlation between δ 49 Ti values and MgO concentrations among aubrites is interpreted to be the result of isotope fractionation driven by the different oxidation states of Ti in this environment, such that isotopically heavy Ti 4+ was concentrated in the residual liquid during magmatic differentiation. Finally, KREEPy impact melt breccia SaU 169 exhibits a heavy δ 49 Ti value of +0.330 ± 0.034‰ which is interpreted to result from Ti isotopic fractionation during ilmenite precipitation in the late stages of lunar magma ocean crystallization. A Rayleigh distillation calculation predicts that a δ 49 Ti value of +0.330‰ is achieved after removal of 94% of Ti in ilmenite.